If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3y + 5x + -2y + -4y = 0 Reorder the terms: 2x + 5x + 3y + -2y + -4y = 0 Combine like terms: 2x + 5x = 7x 7x + 3y + -2y + -4y = 0 Combine like terms: 3y + -2y = 1y 7x + 1y + -4y = 0 Combine like terms: 1y + -4y = -3y 7x + -3y = 0 Solving 7x + -3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 7x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 7x + 0 = 0 + 3y 7x = 0 + 3y Remove the zero: 7x = 3y Divide each side by '7'. x = 0.4285714286y Simplifying x = 0.4285714286y
| 3(2x+5)=47 | | -6x-3+4x=13 | | x^3+3x^2+3x+1= | | x^5-3x^3+4x^2-1=0 | | -(.2-.4x)-.4=x-1.47 | | F(x)=.4x-1 | | 10+5=35 | | 4x+14=-10-27 | | 10+-5=35 | | -3+14=5 | | 4w-45=7(w-3) | | 15=3x-18-85 | | 25x+35y=90 | | 2x+7=32.5 | | 8x-6=20-4x | | F(5)=11-7(5) | | 2x-y=3fory | | 10=8x+5.2 | | 6X-11=-7X+5 | | F(x)=3x^3-12x^2-15x | | 6A+2=4A-12 | | 32=16+b | | 6M+5=3M-10 | | 12=2v | | y=3x-01 | | 5x=-2(5x-15) | | 4A-6=2A+12 | | q+14=9(q+7) | | a^3x-a^2-4ax+4=0 | | -2x-10i=12+(30y)i | | 2x+x+3=6x-3x+3 | | 7A+4=8A-17 |